Being Church in the World as Sacramentum Mundi: Revisioning the Notion of the Church as Sacrament in View of the Sacramentality of the World - Borgman, Erik (Concilium, 2025)
This article starts by arguing that not only because of the struggle during the reformation, but also because of the growing dominance of nominalist philosophy, sacraments were regarded as signs and instruments of God's presence to the world. The sacraments were no longer considered as expressions of God's effective will to remain close to his people, and the Church as both an effect of God's grace enabling human beings to respond to God's presence. That the latter is a good starting point of thinking about Gods presence was discovered in the wake of the Second Vatican Council, not just by theologians like Otto Semmelroth (1912-1979) and Edward Schillebeeckx (1914-2009), but also in spirituality. This marked two important changes in thinking about God and his presence. Firstly, it stressed the hiddenness of this presence, signifying God's connection with the people usually not in the center of attention in society and culture. Secondly, it stressed the fact that it is not the power of the church or its ministers, but God's goodness, his faithfulness to his creation and his trust in its goodness that keeps God actively present to the world.